The Rail Freight Tariffs: The Theoretical Basis of the Transition from the Traditional Formation for Agent-based Modeling - Fisenko, Andrei I.; Komarova, Valentina V.; Nekrasova, Olesya I.; Milai, Alexsandra V. (International Journal of Economics and Financial Issues, 2016)
The paper studies the concept, the basic methods, tools, and tendencies of behavioral economics (BE) along with the possibility of using its methodological and cognitive resources for making rail cargo rates. Philosophical analysis was held of criteria and limitations of BE in the context of its actual use in forming a new methodological approach to the calculation of competitive rail cargo tariffs in the quasi-liberal economy of Russia. It was shown that current methods of the cargo tariffs calculation in modern conditions of rail transport development in Russia are unworkable in the nearest future. Keywords: behavioral economics, rail cargo tariffs, quasi-liberal economics, agent-based modeling, economic behavior JEL Classifications: D7, L9, R1, R4